ВІДПОВІДАЛЬНІСТЬ ЯК ОДНА З ВНУТРІШНЬООСОБИСТІСНИХ ДЕТЕРМІНАТ СОЦІАЛЬНО-КОМУНІКАТИВНОЇ АКТИВНОСТІ ПІДЛІТКІВ (Педагогіка вищої та середньої школи, 2008)
The article is discovered understanding of „responsibility” of teenager's personality in process of touristic activity in the educational process in the comprehensive school